Solve x2 - 16x + 60 = -12 by completing the steps. First, subtract 60 from each side of the equation. Next, add to each side of the equation to complete the square.

Answers

X^2 - 16x + 60 = -12 x^2 - 16x =  -12 - 60 x^2 - 16x + 64 = -72 + 64 (x - 8)^2 = -8 x - 8 = +/- sqrt8 i x = 8 + sqrt8 i  , 8 - sqrt8 i


0 0

X^2 - 16x + 60 = -12 x^2 - 16x =  -12 - 60 x^2 - 16x + 64 = -72 + 64 (x - 8)^2 = -8 x - 8 = +/- sqrt8 i x = 8 + sqrt8 i  , 8 - sqrt8 i


0 0
Only authorized users can leave an answer!
Can't find the answer?

If you are not satisfied with the answer or you can’t find one, then try to use the search above or find similar answers below.

Find similar answers


More questions